Design Optimization and in-vitro Verification of a Bone-Retentive Device to Repair Comminuted Radial Head Fractures - Gasant, Muhammad Saadiq (Department of Human Biology, 2020)
Introduction: Radial head fractures are common, accounting for approximately 30% of all elbow fractures. Mason type III fractures involve comminuted fractures of the radial head, with two or more articular fragments. There is conflict in the literature regarding optimal surgical treatment of these fractures. Current protocol indicates a preference towards bone retention, as this has a minimal impact on the elbow biomechanics. Thus, the preferred surgical open reduction and fixation (ORIF) methods which involve stabilizing the fracture using metal plates and screws. The main drawbacks of this method involve failure of fixation, particularly in more severely comminuted fractures. In these cases, revision surgery is needed. In addition, the metal ware interferes with surrounding tendons and ligaments, leading to discomfort. However, should the fracture be too severe for ORIF repair, the radial head is excised and replaced by a prosthesis. Unfortunately, this affects the biomechanics of the elbow and a loss of motion and strength is likely to result. Thus, there is need for a novel way of treating complex fractures of the radial head. The RadFix™ Fracture Fixation Solution was conceptualized to improve functional healing for these fractures. The concept involved three treatment options which focused on native bone retention and the preservation of radio-capitellar articulation and included a contingency plan in the event of failure of fixation. The main benefit of the device involved the concept of a central stem component and a partial prosthesis, which aimed to replace only the damaged portions of the radial head, whilst preserving the intact native bone. It is hypothesized that this will aid functional healing of the radial head. Aim The aim of the study is to optimize the existing design and experimentally verify the stability of a novel fixation device for comminuted radial head fractures to increase native bone retention. Methodology The existing anatomic prototypes were optimized to include different radial head sizes using Solidworks 3D-modelling software after which prototypes were manufactured from Nylon 12 at the Central University of Technology (CUT). A first pilot test was conducted to evaluate these prototypes - a stem and half-head prosthesis were implanted into a cadaver arm in a procedure which mimicked fracture to the lateral half of the radial head. Radiographic evaluation of the fixation showed stability of the prosthetic components. Recommendations for further development included remodelling the anatomic shape of the prosthetic heads to a generic shape (to allow repair to any quadrant of the radial head) and the development of a drill assist device to aid in the drilling process for stem implantation. The subsequent design modifications were made to the prosthetic head design and a drill assist guide was developed to aid in the relevant surgical processes. These new generic prostheses were 3D-printed from ABS plastic and were evaluated in a second pilot test. Once again, a stem and a half-head prosthetic head were implanted into a cadaver arm after a fracture to the radial head was imitated. Radiographic evaluation of the fixation showed that stability was achieved but that the drill assist device required modifications to its drill guide attachment and stabilizing mechanism. Once the modifications were completed, five more cadaver arms were used to conduct a wider scale study, in which one-third head, half head and full head prostheses were implanted. Each repair was radiographically evaluated before the subsequent repair was performed. Radiographic stabilization involved the evaluation of prosthesis reduction - a measurement of gaps between the prosthetic heads and the adjacent bone (gaps smaller than 2mm were acceptable, gaps bigger than 2mm were not) and an evaluation of screw fixation - optimal screw position involved penetration of cortical bone whilst any protrusion of a screw from the bone was not acceptable. Results Cadaver Arm 1 was used to conduct a half-head prosthetic repair followed by a full-head prosthetic repair. Radiographic analysis of the half-head repair showed that there was correct implant positioning, correct reduction of the prosthesis and correct screw placement. This meant that the repair was classified as successful. The full-head repair was classified as unsuccessful due to a large ulnar-sided overhang and a radial-sided recess, likely caused by movement of the stem during the transition between repairs. Cadaver Arm 2 was used to conduct a one-third head prosthetic repair. Radiographic analysis showed correct implant positioning and correct screw placement, however the repair was classified as unsuccessful due to a 2.04 mm gap between the prosthesis and the adjacent bone on the articular surface of the radial head. Cadaver Arm 3 was used to conduct a one-third head repair, followed by a half-head prosthetic repair and a full-head prosthetic repair. Radiographic analysis classified both the one-third and halfhead repairs as successful. Lastly, radiographic analysis of the full-head prosthetic repair showed that the distal (oblique) screw was too large and protruded from the radial head at both ends, leading to an unsuccessful repair. Cadaver Arm 4 was used to conduct a one-third head repair, followed by a half-head prosthetic repair and a full-head prosthetic repair. Radiographic analysis of the one-third repair saw it classified as successful. The half-head repair was classified as unsuccessful due to a 2.53 mm overhang on the distal-radial edge of the prosthesis. The full-head repair was classified as unsuccessful due to unsuccessful screw placement. Lastly, Cadaver Arm 5 was used to conduct a one-third head prosthetic repair followed by a full-head prosthetic repair. Radiographic analysis of the one-third head repair showed that there was a 2.97 mm gap between the prosthesis and the adjacent bone on the articular surface of the radial head, resulting in an incorrect reduction. This saw the repair classified as unsuccessful. Radiographic analysis of the full-head repair classified it as successful. Conclusion: The aims of the study were successfully completed.